2019
DOI: 10.1016/j.ajoc.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive choroidopathy: Multimodal imaging and the contribution of wide-field swept-source oct-angiography

Abstract: PurposeTo present the case of a patient with a hypertensive choroidopathy and her follow-up using multimodal imaging; and to assess how wide-field swept-source (SS) Optical Coherence Tomography Angiography (OCTA) contributes to detecting the areas of hypoperfusion.ObservationsA 25-year-old white woman with terminal renal insufficiency, myopericarditis, and cerebrospinal fluid pressure of 37 mmHg indicating intracranial hypertension, presented with a painless loss of vision in both eyes. Her blood pressure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
(20 reference statements)
0
14
0
1
Order By: Relevance
“…Polito et al [ 15 ] reported that plasmapheresis could improve the choroidopathy, which indicated the importance of immune complex deposition in the pathophysiology and management strategy of the disease. Secondly, uncontrolled hypertension may cause choroidal vascular occlusions, leading to ischemia and destruction of the external blood-retinal barrier at the RPE[ 16 ]. Thirdly, thrombosis can also lead to choroidopathy by causing microangiopathy[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polito et al [ 15 ] reported that plasmapheresis could improve the choroidopathy, which indicated the importance of immune complex deposition in the pathophysiology and management strategy of the disease. Secondly, uncontrolled hypertension may cause choroidal vascular occlusions, leading to ischemia and destruction of the external blood-retinal barrier at the RPE[ 16 ]. Thirdly, thrombosis can also lead to choroidopathy by causing microangiopathy[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive choroidopathy typically occurs in younger individuals as vascular constriction requires pliable vessels [ 3 ]. Rezkallah et al [ 6 ] described the use of OCTA in a young patient with malignant hypertension to assess choroidal flow loss, which in that particular case was primarily extramacular and likely explained the mild SRF in the macula. In contrast, our patient is older and presented with choroidal flow loss in the central macula and massive central SRF, both of which improved with systemic BP normalization.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Occlusion of small choroidal terminal arterioles and capillaries results in areas of circumscribed choroidal reduced perfusion, which can be visualised as hypofluorescent areas in the early stages of fluorescein angiography (FLA) and indocyanine green angiography (ICGA) [1]. While these areas remain hypofluorescent in the late phase of ICGA, they are visible as multiple hyperfluorescent spots in FLA. OCT-A can also be utilised to visualise reduced blood flow in the choriocapillaris [4]. At biomicroscopic examination, they appear as multifocal, pale-yellow spots in the area of reduced perfusion, particularly in the posterior fundus.…”
Section: Arterial Occlusion Of Smaller Choroidal Vessels and Capillariesmentioning
confidence: 99%
“…Während diese Areale auch in der Spätphase der ICGA hypofluoreszent bleiben, erscheinen sie in der FLA als multiple hyperfluoreszente Flecken. Auch mittels OCT-A lässt sich der reduzierte Blutfluss in der Choriokapillaris darstellen [4]. Biomikroskopisch zeigen sie sich im Bereich der Minderperfusion als multifokale, blass gelbe Flecken, vor allem am hinteren Pol.…”
Section: Arterielle Verschlüsse Kleinerer Aderhautgefäße Und Kapillarenunclassified